2020
DOI: 10.1101/2020.01.31.921130
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss ofslc39a14causes simultaneous manganese deficiency and hypersensitivity in zebrafish

Abstract: 21 Corresponding authors: 22 k.tuschl@ucl.ac.uk, https://orcid.org/0000-0001-8599-8516 23 emb81@cam.ac.uk, https://orcid.org/0000-0001-6450-744X 24 25 Abbreviated title: slc39a14 deficiency causes Mn dyshomeostasis 26 27 Abstract 30Mutations in SLC39A14, a manganese uptake transporter, lead to a neurodegenerative 31 disorder characterised by accumulation of manganese in the brain and rapidly progressive 32 dystonia-parkinsonism (Hypermanganesemia with Dystonia 2, HMNDYT2). Similar to the 33 human phenotype, ze… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Microarray and subsequent cluster analysis demonstrated that 1057 differentially-expressed transcripts, being predominantly involved in regulation of neuronal differentiation and development, apoptosis, and synaptic transmission [ 53 ]. Correspondingly, using zebrafish slc39a14 U801-/- mutants exposed to Mn (50 µM for 72 h) for analysis of differentially-expressed genes demonstrated that the genes associated with Mn neurotoxicity are associated with mitochondrial dysfunction, oxidative stress, apoptosis, lysosomal dysfunction, altered proteostasis and unfolded protein response, Ca 2+ dyshomeostasis, as well as impaired visual phototransduction [ 54 ]. In parallel with the identified gene networks differentially expressed following acute Mn exposure (50 mM for 30 min), metal overload was also found to be associated with modulation of endoplasmic reticulum related genes and lipocalin-related (lpr) family members, thus indicating additional targets for Mn toxicity [ 55 ].…”
Section: Mn-induced Alterations In Subcellular and Multicellular Biologymentioning
confidence: 99%
“…Microarray and subsequent cluster analysis demonstrated that 1057 differentially-expressed transcripts, being predominantly involved in regulation of neuronal differentiation and development, apoptosis, and synaptic transmission [ 53 ]. Correspondingly, using zebrafish slc39a14 U801-/- mutants exposed to Mn (50 µM for 72 h) for analysis of differentially-expressed genes demonstrated that the genes associated with Mn neurotoxicity are associated with mitochondrial dysfunction, oxidative stress, apoptosis, lysosomal dysfunction, altered proteostasis and unfolded protein response, Ca 2+ dyshomeostasis, as well as impaired visual phototransduction [ 54 ]. In parallel with the identified gene networks differentially expressed following acute Mn exposure (50 mM for 30 min), metal overload was also found to be associated with modulation of endoplasmic reticulum related genes and lipocalin-related (lpr) family members, thus indicating additional targets for Mn toxicity [ 55 ].…”
Section: Mn-induced Alterations In Subcellular and Multicellular Biologymentioning
confidence: 99%
“…This group encompasses IMD of amino acid catabolism-like phenylketonuria, maple syrup urine disease, or homocystinuria-, urea cycle defects, organic aciduriaslike methylmalonic or glutaric aciduria type 1-, galactosemia, and metal accumulation-like Wilson disease, neuroferritinopathies and brain iron accumulation syndromes, or hypermanganesemia linked to SLC30A10 and SLC39A14 mutations. [15][16][17] Some small molecules accumulation may lead to visible crystals in diverse tissues like cystine in cystinosis (a lysosomal defect), oxalate in oxalosis (a peroxysomal defect) or homogentisic acid (ochronosis) in alkaptonuria.…”
Section: Accumulation Of Small Moleculesmentioning
confidence: 99%
“…Even though this does not correlate with behavioral changes in the larvae, differential expression of these genes might interfere with other circadianregulated biological pathways during development, such as functioning of the reward and immune systems. It is important to note that differential expression of circadian rhythm genes is reported in other zebrafish RNA-seq experiments (156) and so could be a stress response rather than a drug-evoked response. Glucocorticoid release following stress is also found to induce Per2 expression and cause circadian phase delay (157).…”
Section: Developmental Drug Exposures Induce Differential Expression Of Circadian Genes Some Of Which Show Differential Expression At Latmentioning
confidence: 98%